2001
DOI: 10.1080/08039480152693264
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported competence and emotional and behavioral problems in a sample of Finnish adolescents

Abstract: The Youth Self-Report (YSR) was completed by 586 15- to 16-year-old Finnish adolescents. The internal consistency of the YSR problem scales ranged from 0.61 to 0.90. Girls reported significantly more internalizing, withdrawn, somatic, anxious-depressive thought and attention problems. The adolescent was defined as having maladjustment if he she had used mental health services or had more severe problems than the peer group according to parent or self-report (11% of the sample). There were significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
2
19
2
Order By: Relevance
“…One possible explanation for this might be that girls are expected to do more household chores, have less leisure time, and have restricted freedom compared to boys. In addition, our results indicated that boys had higher scores for delinquent behavior, which is also similar to earlier findings (Helstelä & Sourander, ; Janssen et al ., ; Kapi et al ., ). It is possible that boys' social networks influenced their answers.…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation for this might be that girls are expected to do more household chores, have less leisure time, and have restricted freedom compared to boys. In addition, our results indicated that boys had higher scores for delinquent behavior, which is also similar to earlier findings (Helstelä & Sourander, ; Janssen et al ., ; Kapi et al ., ). It is possible that boys' social networks influenced their answers.…”
Section: Discussionsupporting
confidence: 93%
“…34,35 Also, low response rates with increasing child age are reported. 34,57 A higher proportion of parents of very preterm infants tend to have lower SES than average. We did not have sufficient information at the time of preterm delivery to explore whether parents' SES may have been different between responders and nonresponders.…”
Section: Responders Versus Nonrespondersmentioning
confidence: 98%
“…Otherwise, the missing values were replaced by the mean value of other answered items of the particular subscale. The Finnish version of the YSR has been standardized (Helstelä and Sourander, 2001), and initial support for the generalizability of the YSR syndromes in various societies, including Finland, has been provided (Ivanova et al, 2007).…”
Section: Psychological Symptomsmentioning
confidence: 99%